2010
DOI: 10.1001/jama.2010.608
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Evidence-Based Treatment for Multiple Anxiety Disorders in Primary Care

Abstract: MPROVING THE QUALITY OF MENtal health care requires continued efforts to move evidence-based treatments of proven efficacy into real-world practice settings with wide variability in patient characteristics and clinician skill. 1 The effectiveness of one approach, collaborative care, is well established for primary care depression, 2-5 but has been infrequently studied for anxiety disorders, 6,7 despite their common occurrence in primary care. 8 The multiplicity of anxiety disorders and the fact that anxious pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
383
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 396 publications
(405 citation statements)
references
References 42 publications
12
383
2
6
Order By: Relevance
“…But PTSD treatment is less routine in primary care and its care is more challenging because of barriers at the patient, physician and practice levels. 4,[21][22][23] The Coordinated Anxiety Learning and Management (CALM) trial 24 found that, for patients with PTSD recruited from private and mostly academic medical settings, improvement in outcomes was no different relative to usual care. 25 The Re-Engineering Systems for the Primary Care of PTSD (RESPECT-PTSD) trial for veterans with PTSD did not find an intervention effect for symptoms or functioning.…”
Section: Introductionmentioning
confidence: 99%
“…But PTSD treatment is less routine in primary care and its care is more challenging because of barriers at the patient, physician and practice levels. 4,[21][22][23] The Coordinated Anxiety Learning and Management (CALM) trial 24 found that, for patients with PTSD recruited from private and mostly academic medical settings, improvement in outcomes was no different relative to usual care. 25 The Re-Engineering Systems for the Primary Care of PTSD (RESPECT-PTSD) trial for veterans with PTSD did not find an intervention effect for symptoms or functioning.…”
Section: Introductionmentioning
confidence: 99%
“…(16) The IMPACT trial, one exemplar of collaborative care, demonstrated significant improvement in depression outcomes among elderly patients with cost savings in the long-term. (3) These promising results have engendered considerable national interest in the dissemination of integrated models, and the corresponding need to understand how to implement such models in real-world settings.…”
Section: Introductionmentioning
confidence: 99%
“…The only question is when, how much and whether at some point patients need to be seen in the specialty rather than the primary care setting. This study seems to have used specialty care more than other collaborative care studies (in the large CALM study 6 about half the usual care patients had a specialty care visit), suggesting that it adopted more of a hybrid primary care-specialty care model than other collaborative care studies.…”
mentioning
confidence: 93%
“…Yet the effect size observed in this study was similar to that seen in the largest primary care anxiety study, which used more costly personnel and in-clinic visits and delivered in-person CBT as part of the intervention. 6 How were these small to mid-sized intervention effects achieved with such a bare-bones intervention?…”
mentioning
confidence: 99%
See 1 more Smart Citation